Strategic MICE Venue Management Concept - Mayuree, Wacharakorn; Jaroenwisan, Kaedsiri (Dusit Thani College Journal, 2020)
This article aimed to study strategic management in MICE venues in Thailand through related literature review regarding MICE venues standard management and strategy management. In order to identify the process of strategy creating and also the level of strategy that allows MICE venues to achieve their objectives in terms of the firm performance, competitive advantage, cost saving, and customers satisfaction that will lead to a sustainable development of the venues.